Psychological distress, quality of life, coping and adjustment: a comparison of Oshiwambo-speaking and Sesotho-speaking patients with breast and/or cervical cancer - Shino, Elizabeth Ndeshinuninwa (University of the Free State, 2010)
Psycho-oncology emerged as a formal discipline in the mid-1970s. Much progress has been made in both research and clinical practice, specifically in developed countries. Psycho-oncological research in developing countries, including Africa, remains scant. Cancer has been viewed as a disease of the western world. However, it is estimated that by the year 2020 cancer incidence in developing countries will surpass that of the developed countries. Given this reality and the high mortality from cancer in Africa, the development and progression of psycho-oncology on the continent is essential to provide a basis for research and clinical practice. Against this background, this exploratory and comparative study aimed to investigate psychosocial aspects of cancer patients in two southern African countries. The major objective of the current study was five-fold. Firstly, to provide an overview of psycho-oncology research in Africa, with a brief historical perspective of international psycho-oncology. Secondly, the study explored the presence of psychological morbidity in Oshiwambo-speaking Namibian and Sesotho-speaking South African cancer patients. Additionally, the feasibility of the use of a single-item visual analogue screening instrument of psychological distress was explored. Thirdly, the study explored quality of life (QoL) of cancer patients in these two groups. The association of QoL and psychological distress was also explored. Fourthly, the study explored perceived selfefficacy for coping with cancer in these two countries. Fifthly, adjustment to cancer was explored. By its nature of being a comparative study, Oshiwambo-speaking Namibian and Sesotho-speaking South African patients were compared with regards to psychological morbidity, QoL, self-efficacy for coping and adjustment to cancer. The Distress Thermometer (DT), Hospital Anxiety and Depression Scale (HADS), 26-item World Health Organization Quality of Life measure (WHOQOL-Bref), Cancer Behavior Inventory (CBI) and Mental Adjustment to Cancer (MAC) scale were used. The sample consisted of 103 Namibian and 126 South African patients with a histologicallyconfirmed diagnosis of breast or cervical cancer. Results suggest that a DT cut-off of 3 is the ideal cut-off score for both groups. Using this DT cut-off, approximately half of the patients in both countries reached the case criteria for psychological distress, while a third were identified as distressed on the HADS. About a third scored above the HADS anxiety cut-off. Approximately 30% South African and 20% Namibian patients met the depression case-criteria. With regards to QoL, Namibian and South African patients in this study appeared to have comparable QoL on most domains. However, Namibian patients appeared to fare better on the psychological domain. Psychological distress, anxiety and depression correlated negatively with all facets of QoL. Results suggest overall high self-efficacy for coping with cancer for the entire study sample, and the Namibian group obtaining significantly higher scores. Self-efficacy correlated negatively with psychological morbidity and positively with QoL for both groups of patients. Correlations with psychological morbidity were stronger for South Africa, and comparable for QoL. Namibian and South African patients reported comparable and probably high levels of hopelessness/helplessness responses to a diagnosis of cancer. Fighting spirit correlated negatively with psychological morbidity for both groups, however the magnitude of the correlations were statistically different. Helplessness/hopelessness correlated positively with psychological morbidity. Anxious preoccupation, fatalism and avoidance responses yielded mixed and conflicting results for this study. QoL and self-efficacy correlated positively with a fighting spirit response. This study highlights the presence of psychological morbidity among cancer patients in southern Africa, and supports international research. It further highlights relationships between psychological distress, QoL, self-efficacy for coping and adjustment to cancer. The results could have implications with regard to clinical practice within Namibian and South African oncology settings. However, psychological interventions must take into account geo-socio-cultural differences of cancer patients in the various African oncology settings. Further research in African psycho-oncology research is recommended.

Psigo-onkologie het tydens die middel 1970’s as ŉ formele dissipline na vore getree. Sedertdien het dit baie vordering gemaak wat navorsing en die kliniese praktyk betref, veral in ontwikkelde lande. Psigo-onkologiese navorsing in ontwikkelende lande, insluitend Afrika, is egter nog in sy kinderskoene. Kanker word beskou as ŉ siekte van die Westerse wêreld. Dit is ongeag die beraming dat die insidensie van kanker in ontwikkelende lande teen 2020 dié van ontwikkelde lande sal oortref. Gegewe hierdie realiteit en die hoë kankermortaliteitsyfer in Afrika, is die ontwikkeling en progressie van psigo-onkologie op hierdie kontinent noodsaaklik om ŉ basis vir navorsing en kliniese praktyk te bied. Teen die agtergrond het hierdie verkennende en vergelykende studie ten doel om psigososiale aspekte van kankerpasiënte in twee suider-Afrikalande te ondersoek. Die studie het vyf hoofdoelwitte. Eerstens, om ŉ oorsig te gee van psigo- onkologiese navorsing in Afrika, insluitend ŉ kort historiese perspektief van internasionale psigoonkologie. Tweedens, die studie ondersoek die aanwesigheid van psigologiese morbiditeit in Oshiwambo-sprekende Namibiese en Sesotho-sprekende Suid-Afrikaanse kankerpasiënte. Daarby is die gebruik van ŉ enkel-item visuele analoog siftingsinstrument vir psigiese ontsteltenis ondersoek. Derdens ondersoek die studie die lewenskwaliteit (LK) van die kankerpasiënte in die twee groepe. Die verband tussen LK en psigiese ontsteltenis is ook ondersoek. Vierdens ondersoek die studie die belewing van selftoereikendheid om kanker te hanteer. Vyfdens is aanpassing by kanker nagevors. Omdat dit ŉ vergelykende studie is, is Oshiwambo-sprekende Namibiese en Sesothosprekende Suid-Afrikaanse pasiënte vergelyk ten opsigte van sielkundige morbiditeit, LK, selftoereikendheid om kanker te hanteer en aanpassing by kanker. Die Distress Thermometer, die Hospital Anxiety and Depression Scale (HADS), ŉ 26-item Lewenskwaliteit-instrument (WHOQOL-Bref), die Cancer Behavior Inventory (CBI), asook die Mental Adjustment to Cancer (MAC) is gebruik. Die steekproef het bestaan uit 103 Namibiese en 126 Suid-Afrikaanse pasiënte met ŉ diagnose van bors-of servikale kanker wat histologies bevestig is. Die resultate dui daarop dat DT-afsnypunt van 3 ŉ ideale norm vir albei groepe is. Met hierdie afsnypunt voldoen ongeveer die helfte van die pasiënte in albei lande aan die gevallekriteria vir psigiese ontsteltenis, terwyl een-derde as psigies ontsteld op die HADS identifiseer is. Ongeveer 30% Suid-Afrikaanse en 20% Namibiese pasiënte het aan die gevallekriteria van depressie voldoen. Wat die LK betref, het Suid-Afrikaans en Namibiese pasiënte in die meeste domeine soortgelyke tellings behaal. Namibiese pasiënte het egter beter op die psigologiese domein presteer. Psigiese ontsteltenis, angs en depressie het negatief met alle aspekte van die LK gekorreleer. Die resultate dui daarop dat die totale steekproef ŉ algemene hoë selftoereikendheid openbaar om kanker te hanteer, met die Namibiese groep wat beduidende hoer tellings behaal. Selftoereikendheid het negatief gekorreleer met psigologiese morbiditeit en positief met LK wat albei groepe pasiënte betref. Korrelasies vir psigologiese morbiditeit was sterker vir die Suid-Afrikaners en soortgelyk vir die LK. Namibiese en Suid- Afrikaanse pasiënte het soortgelyke en waarskynlik hoë vlakke van moedeloosheid/hulpeloosheid rakende ŉ diagnose vir kanker getoon. ŉ Veggees korreleer negatief met psigologiese morbiditeit vir albei groepe, hoewel die impak van die korrelasies statisties verskil het. Hulpeloosheid/moedeloosheid het positief met psigologiese morbiditeit. Angstige preokkupasie, fatalisme en vermydingresponse het gemengde resultate aan die lig gebring. LK en selftoereikendheid het positief met ŉ veggees-respons korreleer. Hierdie studie beklemtoon die aanwesigheid van psigologiese morbiditeit by kankerpasiënte in suidelike Afrika en sluit by internasionale navorsing aan. Dit onderstreep ook korrelasies tussen psigiese ontsteltenis, LK, selftoereikenheid om kanker te hanteer en daarby aan te pas. Die resultate kan implikasies vir die kliniese praktyk in die Namibiese en Suid-Afrikaanse onkologiese opset inhou. Sielkundige intervensies moet egter geo-sosio-kulturele verskille by kanker pasiënte in die verskillende onkologieopsette in Afrika in ag neem. Verdere psigo-onkologiese navorsing in Afrika word aanbeveel.
Thesis (Ph.D. (Psychology))--University of the Free State, 2010
Keywords: Psychotherapy; Quality of life; Depression, Mental; Psycho-oncology; Psychological distress; Coping; Self-efficacy; Adjustment; Cancer -- Psychological aspects; Stress (Psychology) -- South Africa; Stress (Psychology) -- Namibia; Oncology -- South Africa; Oncology -- Namibia